Volatile composition, colour, and sensory quality of spirit-based beverages enriched with medicinal fungus Ganoderma lucidum and herbal extract - Veljović, Sonja P. (Array, 2019)
The multicomponent mixtures consisting of herbs and fungi are commonly used for the production of alcoholic beverages with potential health-promoting effects in many Asian countries. The medicinal fungus Ganoderma lucidum is one of the most important fungi used for spirit production. Although this fungus affects the aromatic complexity of spirits, only a small number of studies have focused on investigating the influence of G. lucidum on the aromatic profile and colour of spirits. The aim of the research is to evaluate the influence of adding G. lucidum and herbal extract on final concentrations of volatile compounds and sensory quality of several distillates. In this study, distillates (grain, plum, grape and wine) were used to produce new spirit-based beverages with the fungus G. lucidum only, or with the fungus and herbal extract. Fifty-nine aroma compounds were identified by GC-MS. The aromatic profiles were strongly influenced by the primary aromas of the distillates, but the addition of G. lucidum and herbal extract enriched the volatile fraction of distillates with a range of ethyl esters, with a fruity and floral fragrance. Higher alcohols, 1-propanol, 2-isobutanol and isoamyl alcohol, were the most abundant volatile compounds in the analyzed distillates and spirits. The lightness of distillates was from 60.7 to 63.6, and with the addition of Ganoderma it significantly decreased to the range from 43.6 to 50.5. The addition of the fungus also increased the intensity of red and yellow colours. The Ganoderma spirits scored very highly in sensory evaluation (17.6–18.3), significantly better than the spirits without any additions (16.1–16.9).